Safety evaluation of the food enzyme glucan 1,4‐α‐glucosidase from the non‐genetically modified Aspergillus niger strain NZYM‐BO - EFSA Panel on Food Contact Materials; Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme glucan 1,4‐α‐glucosidase (4‐α‐d‐glucan α‐glucohydrolase; EC 3.2.1.3) is produced with the non‐genetically modified Aspergillus niger strain NZYM‐BO by Novozymes A/S. It was considered free from viable cells of the production organism. It is intended to be used in seven food manufacturing processes: baking processes, brewing processes, cereal‐based processes, distilled alcohol production, fruit and vegetable processing for juice production, production of dairy analogues and starch processing for the production of glucose syrups and other starch hydrolysates. Since residual amounts of total organic solids (TOS) are removed by distillation and during starch processing, dietary exposure was not calculated for these two food manufacturing processes. For the remaining five food manufacturing processes, dietary exposure to the food enzyme–TOS was estimated to be up to 2.97 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1,920 mg TOS/kg bw per day, the highest dose tested, which, when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 646. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and one match with a respiratory allergen was found. The Panel considered that, under the intended conditions of use, the risk of allergic reactions by dietary exposure to this food enzyme cannot be excluded (except for distilled alcohol production), but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.